Family, Work and Well-Being Emergence of New Issues (SpringerBriefs in Well-Being and Quality of Life Research,, 2018)
This book analyses the current state-of-the-art research on families, working hours and well-being in Europe, addressing both paid and non-paid work from a family perspective, and introducing emerging issues related to working hours and family life. Further, it discusses the implications of these issues for the well-being of individuals and families. Examining topics such as the division of paid and non-paid work within families, flexibility patterns, the 24/7 society, intensification of work, and the implication of mobile technology for work-family relations, it illustrates how the experiences of working families differ depending on their socio-economic status .